Culture counts: The diverse effects of culture and society on mental health amidst COVID-19 outbreak in Australia - Furlong, Yulia; Finnie, T. (2020)
Since COVID-19 first emerged internationally, Australia has applied a number of public health measures to counter the disease' epidemiology. The public heath response has been effective in virus testing, diagnosing and treating patients with COVID-19. The imposed strict border restrictions and social distancing played a vital role in reducing positive cases via community transmission resulting in 'flattening of the curve'. Now is too soon to assess the impact of COVID-19 on people's mental health, as it will be determined by both short- and long-term consequences of exposure to stress, uncertainty, loss of control, loneliness and isolation. The authors explored cultural and societal influences on mental health during the current pandemic utilising Geert Hofstede's multidimensional construct of culture and determined psychological and cultural factors that foster resilience. We also reflected on the psychological impact of the pandemic on the individual and the group at large by utilising Michel Foucault' and Jacques Lacan' psychoanalytic theories. Remote Aboriginal Australian communities have been identified as a high-risk subpopulation in view of their unique vulnerabilities owing to their compromised health status, in addition to historical, systemic and cultural factors. Historically, Australia has prided itself in its multiculturalism; however, there has been evidence of an increase in racial microaggressions and xenophobia during this pandemic. Australia's model of cultural awareness will need to evolve, from reactionary to more reflective, post COVID-19 pandemic to best serve our multicultural, inclusive and integrated society.